KNOWLEDGE, ATTITUDE AND PRACTICE FOR EXCLUSIVE BREASTFEEDING AMONG MOTHERS IN WEST BANK: A CROSS -SECTIONAL STUDY - Ateyeh, Remaa (An-Najah National University, 2025)
Background: Exclusive breastfeeding is crucial for the health and growth of both infants and mothers. Aim of Study: This study aims to assess the knowledge, attitude, and practice (KAP) regarding exclusive breastfeeding among mothers in North Westbank, Palestine. Methodology: A quantitative, descriptive cross-sectional design was employed, involving 350 mothers who participated through a self-administered questionnaire. Data were analyzed using SPSS. Results: The correlation analysis conducted on breastfeeding knowledge and demographic factors among mothers revealed significant insights, with a strong positive correlation of 0.55 identified between the belief that breast milk is superior to formula and overall knowledge levels. This indicates that mothers who recognize the benefits of breast milk tend to have a higher understanding of breastfeeding. Additionally, the belief that breastfeeding benefits both mother and child showed a robust correlation of 0.50, suggesting that awareness of mutual benefits reinforces knowledge about breastfeeding practices. Other notable correlations include 0.52 with the belief that breastfeeding helps prevent respiratory infections and 0.42 regarding the sufficiency of breast milk during the first six months. Conversely, negative correlations were identified, such as the belief that women with small breasts cannot produce enough milk, which had a correlation of -0.25, indicating that dispelling such misconceptions can empower mothers and potentially increase breastfeeding rates. The analysis also revealed that 78.6% of mothers expressed a positive attitude towards breastfeeding, with 85.7% indicating a strong intention to breastfeed future children. The ANOVA test results indicated significant differences in breastfeeding knowledge and practices among different age groups, with an F-value of 12.00 for knowledge and 15.00 for practices, both with significance levels below 0.001. These findings underscore the necessity for targeted educational interventions to improve knowledge and support breastfeeding practices among mothers in the West Bank. Conclusion: Despite the generally positive attitude towards exclusive breastfeeding, the analysis highlights a concerning gap in knowledge among mothers. The significant correlations between beliefs and knowledge levels suggest that enhancing educational efforts could empower mothers with the necessary understanding to improve breastfeeding practices. Addressing misconceptions and providing targeted information may lead to better outcomes in breastfeeding initiation and duration, ultimately benefiting both mothers and their children. Recommendations: The study recommends that the Ministry of Health provide training courses on breastfeeding, Palestinian universities update their primary health care programs, and further research be conducted on breastfeeding, particularly in the Gaza Strip and southern West Bank.
المعرفة والمواقف والممارسة للرضاعة الطبيعية الحصرية بين الأمهات في الضفة الغربية: دراسة مقطعية